2021
DOI: 10.1186/s13690-021-00570-y
|View full text |Cite
|
Sign up to set email alerts
|

Youth sport participation and physical activity in rural communities

Abstract: Background Physical activity, a high-frequency health behavior, varies by where children live, learn, and play. Children accumulate physical activity in adult-led in-school and out-of-school settings. Youth sport is a potential setting for physical activity, but there are differences in youth sport participation based on age, sex, and socioeconomic status. There is a gap in understanding demographic influences on youth sport participation and how these factors interact to influence physical act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 38 publications
4
26
0
1
Order By: Relevance
“…While there were no significant differences in MVPA in terms of grade and race, the results indicate the overall daily average minutes of MVPA to be lower than recommended levels for this population. A recent population PA surveillance study also found that females and particularly middle school females (i.e., sixth grade) reported lower levels of PA than males [ 16 , 17 ]. Furthermore, our study indicated that there were no statistically significant PA levels based on age/grade level.…”
Section: Discussionmentioning
confidence: 99%
“…While there were no significant differences in MVPA in terms of grade and race, the results indicate the overall daily average minutes of MVPA to be lower than recommended levels for this population. A recent population PA surveillance study also found that females and particularly middle school females (i.e., sixth grade) reported lower levels of PA than males [ 16 , 17 ]. Furthermore, our study indicated that there were no statistically significant PA levels based on age/grade level.…”
Section: Discussionmentioning
confidence: 99%
“…The sport participation items were informed by sport survey items that had been validated or used in previous studies of youth sport participation. ( Batista et al, 2019 , Kellstedt et al, 2021 , Logan et al, 2020 , Mooses and Kull, 2020 , Woods et al, 2020 ) Parents were asked whether their child participated in organized sports during the pandemic (defined above), yes/no. Organized sports were defined as leader-directed physical activity involving rules, practice, and competition.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a recent study found that rural residents were less interested in recreational sports than urban residents. Similarly, a study examined factors associated with youth sport participation and found that children in rural communities experienced more constraints of sport participation than those living in urban communities [ 38 ]. Chick et al [ 39 ] found that older people listed constraints related to age and health more frequently than younger people while younger informants were more concerned with resources such as money in the urban Taiwanese.…”
Section: Literature Reviewmentioning
confidence: 99%